Gerenciamento de riscos em contratos de startups e empresas de base tecnológica - Leonardecz, Alessandra Redua (2017)
The ability to innovate is crucial to companies and nations competitiveness in a globalized world and the technological innovation may be the main source of business competitive advantage. In this context, startups and technological-based companies can expand. On the other hand, introducing innovations can involve risks. Considering these risks, the present study aims to analyse the risk management in private technological products and services contracts in startups and technological-based companies. This research is of a nature applied to its purpose and descriptive as to the general purpose. To achieve the proposed goals, the bibliographical revision method was used. This study is applied to its purpose and descriptive considering the general purpose. The bibliographical revision method was used to achieve the proposed goals. As result, it was identified that it is possible to analyze products/technological purchase and sale contracts risk management signed with a Startup or technology-based company through the PMBOK guide especially through the application and elaboration of a risk probability matrix. Also that the proximity of the PMBOK guide with the law economic analysis can increase the legal certainty of products/technological services purchase and sale contracts signed with a Startup or technological-based companies, reducing the risks from this transaction.